Pemberdayaan Masyarakat Melalui Pelatihan Hidroponik Untuk Membentuk Wirausaha Baru Bernilai Ekonomi - Herawati Khotmi; Agus Fahrul Chair; Baehaki Syakbani; Sukma Hidayat Kurnia Abadi; Mustaan Mustaan; Sofiati Wardah; I Made Murjana (Joong-Ki : Jurnal Pengabdian Masyarakat, 2022)
Abstract: The training activities are based on the collaboration between the dedication team and Mandiri Bank. All activities are sponsored by Mandiri Bank. The purpose of this activity through Mandiri Bank is to foster civil servants who are about to or nearing retirement to take part in hydroponic cultivation training. In this case, Mandiri Bank provides facilitation in terms of providing funding for those who want to develop a hydroponic plant cultivation business. The activity was carried out in the North Lombok Regency Regent's Office Hall. The method of implementing the activities carried out is in the form of training on hydroponic plants along with teaching aids to facilitate understanding of hydroponic plant cultivation. The activity was made as interesting as possible, considering that the activity was carried out during the day so that a quiz or some kind of game was held to encourage the participants. In addition, the contents of this hydroponic cultivation training provide a guide regarding opportunities for business development and/or being able to cultivate hydroponic plants in the yard of the house for daily consumption. The enthusiasm of the participants was very good, as seen by approximately 50% preferring hydroponic cultivation to train other than hydroponic cultivation such as catfish and moringa cultivation.